2018
DOI: 10.1016/j.bonr.2018.04.001
|View full text |Cite|
|
Sign up to set email alerts
|

Distal radius microstructure and finite element bone strain are related to site-specific mechanical loading and areal bone mineral density in premenopausal women

Abstract: While weight-bearing and resistive exercise modestly increases aBMD, the precise relationship between physical activity and bone microstructure, and strain in humans is not known. Previously, we established a voluntary upper-extremity loading model that assigns a person's target force based on their subject-specific, continuum FE-estimated radius bone strain. Here, our purpose was to quantify the inter-individual variability in radius microstructure and FE-estimated strain explained by site-specific mechanical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…The compressive force applied during this simple task is measured using a uniaxial load cell and simulated using a CT-based FE model of the radius, scaphoid and lunate. We have shown that among premenopausal women with normal bone mineral density (T-score [−2.5,1.0]), bone strain, which stimulates bone adaptation, is highly variable even when the same external force is applied to the hand ( Figure 3 ) [ 80 ]. We believe that in the future, exercise interventions would be more successful if individual differences in anatomy were considered, to generate specific bone strains.…”
Section: Emerging Areas Of Research About Exercise and Women’s Bonmentioning
confidence: 99%
“…The compressive force applied during this simple task is measured using a uniaxial load cell and simulated using a CT-based FE model of the radius, scaphoid and lunate. We have shown that among premenopausal women with normal bone mineral density (T-score [−2.5,1.0]), bone strain, which stimulates bone adaptation, is highly variable even when the same external force is applied to the hand ( Figure 3 ) [ 80 ]. We believe that in the future, exercise interventions would be more successful if individual differences in anatomy were considered, to generate specific bone strains.…”
Section: Emerging Areas Of Research About Exercise and Women’s Bonmentioning
confidence: 99%
“…( Tsuji et al, 1995 )). We previously reported that nondominant distal radius cross-sectional area was positively correlated with age, height, and grip strength in a large subset of this cohort ( Mancuso et al, 2018 ). Here, we confirm that these relationships are similar in both the dominant and nondominant forearms.…”
Section: Discussionmentioning
confidence: 74%
“…A previous theoretical study suggested that a 10% increase in peak bone mass would result in an additional 13 years of osteoporosis-free life ( Hernandez et al, 2003 ). We recently showed that a 1 SD (11%) increase in areal bone mineral density (aBMD) at the distal radius was associated with a 20% increase in bone stiffness ( Mancuso et al, 2018 ). Twenty to 40% of peak bone mass is modifiable through lifestyle factors ( Weaver et al, 2016 ) including sports participation and other bone-loading physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…The compressive force applied during this simple task is measured using a uniaxial load cell and simulated using a CT-based FE model of the radius, scaphoid and lunate. We have shown that among premenopausal women with normal bone mineral density (T-score [-2.5,1.0]), bone strain, which stimulates bone adaptation, is highly variable even when the same external force is applied to the hand (Figure 3) [71]. We believe that in the future, exercise interventions would be more successful if individual differences in anatomy were considered, to generate specific bone strains.…”
Section: Measuring Bone Loading In Vivomentioning
confidence: 99%